Comparative Cost-Effectiveness Analysis to Inform Policy in Developing Countries: A General Framework with Applications for Education - Dhaliwal, Iqbal; Duflo, Esther; Glennerster, Rachel; Tulloch, Caitlin (Education policy in developing countries, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:DG9Q8TQF 2405685:YEG3692Q

Education's Effects on Individual Life Chances and On Development: An Overview - McMahon, Walter W.; Oketch, Moses (British Journal of Educational Studies, 2013)
This paper estimates the effects of human capital skills largely created through education on life's chances over the life cycle. Qualifications as a measure of these skills affect earnings, and schooling affects private and social non-market benefits beyond earnings. Private non-market benefits include better own-health, child health, spousal health, infant mortality, longevity, fertility, household efficiency, asset management and happiness. Social benefits include increased democratisation, civil rights, political stability, reduced crime, lower prison, health and welfare costs, and new ideas. Individual benefits enhance community-wide development. New ‘narrow’ social rates of return using UK Labour Force earnings correct for institutional costs, longitudinal trends and ability. The paper's objective, however, is to estimate these earnings plus non-market outcomes comprehensively without overlaps and also relative to costs. Non-market outcomes are measured by averaging regression coefficients from published studies that meet scientific standards. New UK ‘narrow’ social rates of return average 12.1 per cent for short-cycle and 13.6 per cent for bachelor's programmes. Augmented with non-market effects on life chances, they are over twice that. Short degrees are found effective for regional development and have potential for developing countries.
Publisher: Routledge _eprint: https://doi.org/10.1080/00071005.2012.756170 KerkoCite.ItemAlsoKnownAs: 10.1080/00071005.2012.756170 2339240:4YZ6K9I8 2405685:X94EP2P8
Keywords: ___working_potential_duplicate; cost-benefit; education and development; externalities; financing criteria; life chances; non-market benefits; qualifications; rates of return; social benefits

Education's Effects on Individual Life Chances and On Development: An Overview - McMahon, Walter W.; Oketch, Moses (British Journal of Educational Studies, 2013)
This paper estimates the effects of human capital skills largely created through education on life's chances over the life cycle. Qualifications as a measure of these skills affect earnings, and schooling affects private and social non-market benefits beyond earnings. Private non-market benefits include better own-health, child health, spousal health, infant mortality, longevity, fertility, household efficiency, asset management and happiness. Social benefits include increased democratisation, civil rights, political stability, reduced crime, lower prison, health and welfare costs, and new ideas. Individual benefits enhance community-wide development. New ‘narrow’ social rates of return using UK Labour Force earnings correct for institutional costs, longitudinal trends and ability. The paper's objective, however, is to estimate these earnings plus non-market outcomes comprehensively without overlaps and also relative to costs. Non-market outcomes are measured by averaging regression coefficients from published studies that meet scientific standards. New UK ‘narrow’ social rates of return average 12.1 per cent for short-cycle and 13.6 per cent for bachelor's programmes. Augmented with non-market effects on life chances, they are over twice that. Short degrees are found effective for regional development and have potential for developing countries.
Publisher: Routledge _eprint: https://doi.org/10.1080/00071005.2012.756170 KerkoCite.ItemAlsoKnownAs: 10.1080/00071005.2012.756170 2339240:4YZ6K9I8 2405685:X94EP2P8
Keywords: ___working_potential_duplicate; auto_merged; cost-benefit; education and development; externalities; financing criteria; life chances; non-market benefits; qualifications; rates of return; social benefits

What are the impacts and cost-effectiveness of strategies to improve performance of untrained and under-trained teachers in the classroom in developing countries? Systematic review - Orr, David; Westbrook, Jo; Pryor, John; Durrani, Naureen; Sebba, Judy; Adu-Yeboah, Christine (EPPI-Centre, Social Science Research Unit, Institute of Education, 2013)
KerkoCite.ItemAlsoKnownAs: 2339240:K82B5UP3 2339240:NN7K3HRQ 2405685:5J3HIZH9 2405685:YAT9NL4R
Keywords: C:Low- and middle-income countries

The Challenge of Education and Learning in the Developing World - Kremer, Michael; Brennen, Conner; Glennerster, Rachel (Science, 2013)
Across many different contexts, randomized evaluations find that school participation is sensitive to costs: Reducing out-of-pocket costs, merit scholarships, and conditional cash transfers all increase schooling. Addressing child health and providing information on how earnings rise with education can increase schooling even more cost-effectively. However, among those in school, test scores are remarkably low and unresponsive to more-of-the-same inputs, such as hiring additional teachers, buying more textbooks, or providing flexible grants. In contrast, pedagogical reforms that match teaching to students' learning levels are highly cost effective at increasing learning, as are reforms that improve accountability and incentives, such as local hiring of teachers on short-term contracts. Technology could potentially improve pedagogy and accountability. Improving pre-and postprimary education are major future challenges.
Publisher: American Association for the Advancement of Science KerkoCite.ItemAlsoKnownAs: 10.1126/science.1235350 2339240:67BCHX95 2339240:MUEFL3NF 2405685:PFYKPNHQ 2405685:U4T6SC5D
Keywords: ___working_potential_duplicate

Are contract teachers and para-teachers a cost-effective intervention to address teacher shortage and improve learning outcomes? - Kingdon, Geeta Gandhi; Aslam, Monazza; Rawal, Shenila; Das, Sushmita (Evidence for Policy and Practice Information and Co-ordinating Centre:Social Science Research Unit, Institute of Education, University of London, 2013)
OCLC: 1064447467 KerkoCite.ItemAlsoKnownAs: 2339240:KLB5ET5M 2405685:DIMSNBTN

Learning from international experiences with interactive whiteboards - Hennessy, Sara; London, Laura (OECD, 2013)
This paper describes teacher strategies and experiences with interactive whiteboards (IWBs) and draws on the published research in this area to understand how a systemic approach to technology-based innovations in schools can contribute to quality education for all. It explores ways to support the cultural shift in teacher and learner roles that helps to integrate the technology effectively into classroom teaching. It begins by considering how the features of IWB technology might potentially be exploited in the primary or secondary school classroom to support subject teaching and learning. International experiences of implementing IWB programs are then described, mostly from the United Kingdom where integration efforts are the most prominent, and implications for future intervention efforts are examined. The review concludes by defining the organisational conditions for enhancing teacher commitment and thus the likelihood for successful change. In particular, the role of teacher professional development is foregrounded and characteristics of effective programmes are outlined. Some comments about the relative costs and benefits, and recommendations for policymakers, are made.
KerkoCite.ItemAlsoKnownAs: 2339240:TTB8Z79I 6018420:4TZJWG3F

Computers and the academic performance of elementary school-aged girls in China's poor communities - Yang, Yihua; Zhang, Linxiu; Zeng, Junxia; Pang, Xiaopeng; Lai, Fang; Rozelle, Scott (Computers & Education, 2013)
Experts agree that computers and computing play an important role in education. Since the 1980s there has been a debate about gender as it relates to computers and education. However, results regarding gender differences concerning computer use in education are not consistent. In particular there is little work done in China on this issue. Therefore, the overall goal of this paper is to demonstrate whether girls and boys can gain equally from computer-based education in China's elementary schools. To do so we analyze results from three randomized field experiments of a Computer Assisted Learning (CAL) program and One Laptop Per Child (OLPC) program. The field experiments are carried out in three kinds of schools: Shannxi rural public schools; Qinghai minority public schools; and Beijing migrant schools. Although CAL and OLPC have been considered cost effective means to improve learning outcomes, it is not known whether the programs impact girls differently than boys. Our analysis shows that, in fact, there were no differences between female and male students in either the improvement in standardized math test scores or Chinese test scores with either the CAL or OLPC programs. Our study suggests that among disadvantaged students in China's rural areas and migrant communities, there is reason to believe that computer based learning can benefit both girls and boys equally. This finding has possible implications for China's ongoing efforts to integrate computers and computing technologies into the nation's underserved schools.
shortDOI: 10/f4g6qc KerkoCite.ItemAlsoKnownAs: 10.1016/j.compedu.2012.08.011 10/f4g6qc 2339240:MK5NR7LT 2405685:6XU8AFCQ 2405685:JJ2NC7PA
Keywords: Country-specific developments; Elementary education; Evaluation of CAL systems; Gender studies; Teaching/learning strategies

Computers and the academic performance of elementary school-aged girls in China's poor communities - Yang, Yihua; Zhang, Linxiu; Zeng, Junxia; Pang, Xiaopeng; Lai, Fang; Rozelle, Scott (Computers & Education, 2013)
Experts agree that computers and computing play an important role in education. Since the 1980s there has been a debate about gender as it relates to computers and education. However, results regarding gender differences concerning computer use in education are not consistent. In particular there is little work done in China on this issue. Therefore, the overall goal of this paper is to demonstrate whether girls and boys can gain equally from computer-based education in China’s elementary schools. To do so we analyze results from three randomized ﬁeld experiments of a Computer Assisted Learning (CAL) program and One Laptop Per Child (OLPC) program. The ﬁeld experiments are carried out in three kinds of schools: Shannxi rural public schools; Qinghai minority public schools; and Beijing migrant schools. Although CAL and OLPC have been considered cost effective means to improve learning outcomes, it is not known whether the programs impact girls differently than boys. Our analysis shows that, in fact, there were no differences between female and male students in either the improvement in standardized math test scores or Chinese test scores with either the CAL or OLPC programs. Our study suggests that among disadvantaged students in China’s rural areas and migrant communities, there is reason to believe that computer based learning can beneﬁt both girls and boys equally. This ﬁnding has possible implications for China’s ongoing efforts to integrate computers and computing technologies into the nation’s underserved schools.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.compedu.2012.08.011 2339240:5UDBDTWD 2405685:RZVXC9AE